2002
DOI: 10.1177/112067210201200615
|View full text |Cite
|
Sign up to set email alerts
|

Ladies with Leber's Hereditary Optic Neuropathy: An Atypical Disease

Abstract: All three cases, although not unique, posed considerable diagnostic difficulties over a long period of time. The authors have highlighted important associations of the disease and stress the importance of making the diagnosis in women. They are at increased risk of having affected children, unlike the affected males, especially if they are affected themselves and may wish to seek further genetic advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The clinical features of this 50‐year‐old woman is atypical for LHON. Three female patients with atypical LHON were reported, and the authors reported difficulties in making a diagnosis 3 . Because a delayed onset of LHON has been reported in patients over 60 years old, 4,7 diagnostic confusion may occur in older subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical features of this 50‐year‐old woman is atypical for LHON. Three female patients with atypical LHON were reported, and the authors reported difficulties in making a diagnosis 3 . Because a delayed onset of LHON has been reported in patients over 60 years old, 4,7 diagnostic confusion may occur in older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of Japanese with LHON have the nt 11778 mutation, which is associated with poor visual prognosis 2 . The incidence of atypical cases of LHON has recently increased because genetic diagnosis has become more widely applied 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Such pre-excitation syndromes have been previously observed in families diagnosed with LHON and homoplasmic rather than heteroplasmic changes are typical of this mitochondrial disorder. 19,[27][28][29][30] Only one heteroplasmic mutation with a potential effect on protein function was identified in this patient group. This novel substitution (10677GϾA) was discovered in the NADH dehydrogenase subunit 4L of Patient 13, who was one of a set of dizygotic twins enrolled in the study.…”
Section: Prediction Of Functionally Pathogenic Effectsmentioning
confidence: 89%
“…There is an increased risk of visual loss in males with these mtDNA variants, which is thought to reflect a protective effect of oestrogen in female carriers [56]. Most affected individuals have isolated ophthalmological symptoms, but there may be other clinical features such as dystonia [57] or cardiac conduction problems (Wolff–Parkinson–White) [58], and occasionally, LHON may overlap with Leigh syndrome and/or MELAS [59].…”
Section: Clinical Complexity: Canonical Syndromic Presentations Of Chmentioning
confidence: 99%
“…Sudden death is also a feature of PPA2 mutations, and implantation of a cardiac defibrillator may be life‐preserving in affected individuals [82]. Wolff–Parkinson–White has been reported in LHON, MELAS and Leigh syndrome caused by the m.13513G>A mutation [44,58,83]. Valvular heart disease is a rare feature of mitochondrial disease but has been documented in individuals with mutations in PDSS1 encoding a coenzyme Q 10 biosynthetic enzyme [84].…”
Section: Other Phenotypes: a Systems Approach To Mitochondrial Diseasmentioning
confidence: 99%